International Legal Strategy to Trace and Recover Corrupt Assets Hidden Outside the State Jurisdiction Under UNCAC Provisions - Novelino, Romadu; Sulaiman, Abdullah (Jurnal Greenation Sosial dan Politik, 2025)
Recovery of assets resulting from corruption hidden outside the jurisdiction of a country is a serious challenge in law enforcement and the eradication of corruption globally. The United Nations Convention Against Corruption (UNCAC) as an international legal instrument provides a comprehensive framework to facilitate cooperation between countries in tracing, freezing, and returning corruption assets. This study examines the international legal strategies regulated in UNCAC, including the mechanism of international cooperation, mutual legal assistance, and the principle of recognition and enforcement of foreign judgments. In addition, this study analyzes the implementation obstacles faced by developing countries in accessing cross-jurisdictional asset recovery procedures and the importance of strengthening the capacity of domestic institutions and legal diplomacy between countries. With a normative approach and case studies, this paper aims to identify strategic steps in optimizing asset recovery based on the UNCAC international legal framework.